Pacto nacional pelo fortalecimento do ensino médio e Base Nacional Comum Curricular: análise das propostas de formação continuada de professores de ciências da natureza para o ensino médio - Olmedo, Alessandra dos Santos (2022)
This thesis was developed in the Graduate Program in Science Teaching, linked to the Physics Institute of the Federal University of Mato Grosso do Sul, in the research line of Teacher Training. The question that motivated the research was: How did the Natural Sciences teachers at a State Education Network school, located in the municipality of Dourados, Mato Grosso do Sul (MS), understand the teacher training developed by the National Pact for Strengthening Secondary Education – PNEM - (2014/2015) and the Proposal for the Common National Base for Basic Education Teacher Training – BNCFP - (2018/2020)? In view of this context, the following thesis was formulated: The curricular proposal developed by the National Pact for the Strengthening of Secondary Education (PNEM 2014/2015) presents a better direction for the training of Natural Sciences teachers in the critical-reflexive perspective, when compared to the curricular proposal of the Common National Base for the Training of Basic Education Teachers (BNCFP)? The general objective was to analyze the curricular proposals for the formation of Natural Sciences teachers of the PNEM and BNCFP of Basic Education from the understanding of teachers of a State Network school in the municipality of Dourados (MS) who participated in both the formations. The research participants are six teachers from the area of Natural Sciences (Biology, Physics and Chemistry) of High School working at the field school of study, who answered the structured electronic questionnaire, and who participated in the formation of the PNEM and in the formations proposed for the implementation of the BNCC; this step was possible through the authorization opinion registered in the UFMS Ethics Committee. The theoretical references that supported the research are Freire (2019), Imbernón (2016; 2011; 2010; 2009) and Zeichner (2008; 1993), which provide us with an understanding of the relationship between theory and practice through a critical-reflective bias. Methodological framework, this is a qualitative research, in which data were collected through bibliographical research, documents and questionnaire. And the data were examined using Content Analysis by Bardin (2016) and the IRaMuTeQ software. From the presentation of Booklet I of Stage I “High School and Integral Human Training”, we analyzed this document according to the Content Analysis (CA) proposed by Bardin (2016), where four categories were elaborated a priori: Category I ( CEI) “High School – An institutional historical balance”; Category II (CEII) “Challenges for High School”; Category III (CEIII) “Towards Social Quality Secondary Education”; Category IV (CEIV) “Other challenges to high school public policies”, thus, discussing them in the light of the authors who guide this research as theoretical contributions. With regard to Notebook III of Phase II Natural Sciences, four categories were created a priori for AC four categories: Category I (CCI) “Contextualization”, Category II (CCII) “Subjects High School Students”, Category III (CCIII) “Labour, Culture, Science and Technology” and Category IV (CCIV). “Curricular Pedagogical Approaches”. In such a way that in the analysis of the BNCFP four categories were established a priori for Bardin's AC (2016): Category I (CBI) “Continuing education”, Category II (CBII) “Teachers' References” and Category III (CBII) “Matrix Competencies”. In the results of the bibliographical research of theses and dissertations about the PNEM, it was verified that the advantages pointed out as receiving the scholarship and the moments of discussion, the disadvantages would be the sudden interruption of the program and the ready model of formation. Regarding the theses and dissertations on the BNCFP, the results pointed to the works, dealing at first with the impacts of curricular changes on students and, later, with the need for training processes for teachers. Even in the midst of contradictions, as a result of the political instability that resulted in the sudden interruption of the program, through the analysis of the PNEM documents and the questionnaires, we found confirmation of the thesis of this work, that the PNEM presented better direction for the training of teachers of Natural Sciences in a critical-reflective perspective, when compared with the curricular proposal of the National Common Base for Basic Education Teacher Training (BNCFP).